The Influence of Reproductive Health Education on Menstruation on the Knowledge of Adolescent Girls at SMPN 24 Padang - Hakim, Rahmadini Faricha; Rusdi, Annisa; Putri, Mustika Khasanah; Nurhafiza, Nurhafiza; Aisyah, Siti (International Journal of Applied Counseling and Social Sciences, 2025)
Adolescence is a transitional period characterized by various physical and psychological changes, including menstruation in adolescent girls. Lack of knowledge about menstruation can affect adolescents' behavior in maintaining reproductive health. Menstruation-related reproductive health education can improve adolescents' knowledge. This study aims to determine the influence of reproductive health education on adolescent girls' knowledge about menstruation. This study uses a quantitative design with a pre-experimental, pre-test, and post-test one-group design approach. The sample comprised 58 respondents. Samples were taken by purposive sampling technique. Data was analyzed using the Wilcoxon test. The results showed that most respondents (56.90%) had a low level of knowledge before the intervention. After being given an intervention, knowledge increased as much as (89.6%) of respondents had good knowledge. The results of Wilcoxon's statistical test showed a significant influence of reproductive health education on menstruation on adolescent girls' knowledge level at SMPN 24 Padang (p-value = 0.000).